FRI0436 Fatigue Is Associated with Work Productivity Impairment in Uk Patients with Axial Spondyloarthritis (AXSPA): A Cross-Sectional Observational Study. (15th July 2016) - Espahbodi, S.; Bassett, P.; Tillett, W.; Cavill, C.; Hole, J.; Freeth, M.; Thomas, A.; Sengupta, R.
Abstract : Background: Many patients with axSpA experience work disability (WD: not working due to axSpA) which is preceded by impairment whilst working (presenteeism), absenteeism, and overall work productivity loss (WPL). Studies addressing these and health-related factors are few, with only one done in a UK sample. Objectives: To determine key factors associated with absenteeism, presenteeism, WPL, and daily activity impairment (other than employed work) in UK patients with axSpA using standardized measures. Methods: In a cross-sectional, observational study, during visits to the Royal National Hospital for Rheumatic Diseases axSpA clinic, 490 patients completed validated questionnaires for: (1) Work productivity using the Work Productivity and Impairment questionnaire (WPAI) which produces 4 measures: absenteeism, presenteeism, WPL and activity impairment; (2) Health-related disease factors using: BASDAI, BASFI, BASMI, Jenkins Sleep scale, Patient Global Assessment (PGA) for disease activity, back pain at night, back pain at any time, EQ-5D for mobility, self-care ability, usual daily activities, pain/discomfort, anxiety/depression, EQ-VAS for Health State Today, FACIT for fatigue in the last week scale, and the Margolis Pain Diagram. Statistics package STATA V. 13.1 was used for analyses. Univariate and multivariate linear and logistic regression were applied to determine associations between WPAI measures and health-related factors. Results: Of 490 patients, 301 (61%) provided WPAI measurements, 261 (53%) were in employment, 76% were male, 87% HLA-B27+, mean (±SD) years (i) age of first symptoms 21.5 (8.8), (ii) age at diagnosis 30.8 (11.7), (iii)disease duration 21.7 (13.0), and 29% were receiving biologics. Mean scores: BASDAI 3.8 (2.2), BASFI 4.0 (2.7), BASMI 3.8 (2.1), Jenkins 13.0 (2.7), PGA 3.9 (2.6), PGA night pain 3.3 (2.6), PGA pain anytime 3.6 (2.6), FACIT 34 (12), EQ-VAS 63 (22), Margolis pain 8.7 (6.9). Mean WPAI scores for absenteeism were=5.1% (19.2), presenteeism=22% (24.3), WPL=23.2% (25.7), activity impairment=34.8% (27.3). Conclusions: Work productivity and activity impairment are associated with fatigue, disease activity, and functional ability in UK patients with axSpA. The strong association of fatigue with work disability and activity impairment emphasize the need to measure and better understand the impact of fatigue in axSpA. Disclosure of Interest: None declared